A feasibility study on establishing "Putohan at Meriendahan sa Pinagtipunan" at Pinagtipunan General Trias, Cavite - Saliba, Aldrin J., author; Zoleta, Reus R., author; Viejo, Jaqueline M., author; Ventura, Elizabeth A., adviser (Rosario, Cavite : Cavite State University-CCAT Campus, 2003)
Thesis Abstract
A Feasibility Study (BSHRM)--Cavite State University-CCAT Campus, 2003.
Includes bibliographical references and appendices.
In English text.
Keywords: Snack house; Native Filipino food; Snacks; Merienda; Feasibility study; Delicious snacks; Affordable prices